2018
DOI: 10.1177/0883073818760890
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Fluid Cytokine Levels and Single-Photon Emission Computed Tomography Findings in Complex Febrile Seizures

Abstract: In this study, the authors assessed cerebrospinal fluid cytokine levels and single-photon emission computed tomography (SPECT) findings in complex febrile seizures. This study included 23 Japanese patients with complex febrile seizures. Twenty patients underwent SPECT and 12 underwent analysis of cerebrospinal fluid cytokine levels (interleukin [IL]-6, interleukin-10, interleukin-17, interleukin-1β, tumor necrosis factor-α, and interferon-γ); 9 patients underwent both studies. Cerebrospinal fluid cytokine leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…There are several studies evaluating the CSF IL-10 levels in patients with FS. It has been reported that in 12 patients with complex FS the CSF IL-10 levels in addition to CSF IL-6, IL-1β, and TNF-α levels were significantly lower than in patients with acute encephalopathy [17]. However, in comparison of the patients with only FS and FS with encephalopathy, accompanied with influenza virus infection, there was no difference in the CSF IL-10 levels [18].…”
Section: Discussionmentioning
confidence: 95%
“…There are several studies evaluating the CSF IL-10 levels in patients with FS. It has been reported that in 12 patients with complex FS the CSF IL-10 levels in addition to CSF IL-6, IL-1β, and TNF-α levels were significantly lower than in patients with acute encephalopathy [17]. However, in comparison of the patients with only FS and FS with encephalopathy, accompanied with influenza virus infection, there was no difference in the CSF IL-10 levels [18].…”
Section: Discussionmentioning
confidence: 95%
“…The findings may be due to the small number of cases included in the study rather than represent a more intense involvement of granzyme A in the pathogenesis of acute encephalopathy relative to granzyme B. It is difficult to distinguish between acute encephalopathy and complex febrile seizures, 1,3 -5 and about 40% of patients with acute encephalopathy have been diagnosed with unclassified acute encephalopathy 6 ; therefore, the pathogenesis of acute encephalopathy might have a wide spectrum. We did not determine whether granzymes A and B or the specific cytokines assessed in this study are involved in the apoptosis-related pathogenesis of acute encephalopathy.…”
Section: Discussionmentioning
confidence: 94%
“…Accordingly, complex febrile seizures (cFS) may be indistinguishable from AESD or unclassified acute encephalopathy during the acute phase. 1,3 -5 The difficult classification in these patients is due to several factors, including a lack of remarkable neuroimaging findings. 6 There are recent reports of patients with unclassified acute encephalopathy and mild encephalopathy with transient increases in glutamine, detected with MR spectroscopy.…”
mentioning
confidence: 99%